2008
DOI: 10.1097/fpc.0b013e3282f75f88
|View full text |Cite
|
Sign up to set email alerts
|

CYP3A5 genotype is not associated with a higher risk of acute rejection in tacrolimus-treated renal transplant recipients

Abstract: We conclude that patients expressing CYP3A5 need more tacrolimus to reach target concentrations and have a lower tacrolimus exposure shortly after transplantation. This delay in reaching target concentrations, however, did not result in an increased incidence of early BPAR and therefore, genotyping for CYP3A5 is unlikely to improve short-term transplantation outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
78
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(103 citation statements)
references
References 48 publications
17
78
0
8
Order By: Relevance
“…The majority (85%) of our non-AA population had the CYP3A5*3/*3 genotype, whereas the majority (87%) of the AAs had the CYP3A5*1/*1 or CYP3A5*1/*3 genotype. Despite this, race was insignificant in our final dosing model most likely due to collinearity between CYP3A5 genotype and race.Although the CYP3A5 genotype is associated with tacrolimus CL/F, it is not associated with acute rejection [37][38][39]. The lack of association is not surprising given that multiple factors increase the risk of rejection (i.e.…”
Section: Figurementioning
confidence: 85%
“…The majority (85%) of our non-AA population had the CYP3A5*3/*3 genotype, whereas the majority (87%) of the AAs had the CYP3A5*1/*1 or CYP3A5*1/*3 genotype. Despite this, race was insignificant in our final dosing model most likely due to collinearity between CYP3A5 genotype and race.Although the CYP3A5 genotype is associated with tacrolimus CL/F, it is not associated with acute rejection [37][38][39]. The lack of association is not surprising given that multiple factors increase the risk of rejection (i.e.…”
Section: Figurementioning
confidence: 85%
“…[17] Other investigators have also reported that CYP3A5 expressers do not have a higher risk of developing acute rejection. [18][19][20][21][22][23][24][25][26] Although numerous studies have reported the higher Tac dose requirement of CYP3A5 expressers compared to nonexpressers, the clinical relevance of this association is unclear and has so far only been investigated in two randomized-controlled clinical trials (RCT). The Tactique study [27] was a multicenter RCT, including 280 renal transplant recipients.…”
Section: Genetic Variation and Tac Pharmacokineticsmentioning
confidence: 99%
“…The intrinsic clearance of tacrolimus is approximately 2-fold higher for CYP3A5 than for CYP3A4 (Hesselink et al, 2008). This plasmatic clearance is higher in those individuals with genotype CYP3A5*1/*3 regarding those CYP3A5*3/*3 (Haufroid et al, 2006).…”
Section: Influence On Tacrolimus Pharmacokineticsmentioning
confidence: 88%